Accommodating preference heterogeneity in commuting mode choice: an empirical investigation in Shaoxing, China. Issue 4 (19th May 2017) - Fu, Xuemei; Juan, Zhicai
ABSTRACT: A latent class model is developed to accommodate preference heterogeneity across commuters with respect to their mode choice between electric bike, private car, and public bus within the context of China. A three-segment solution – 'electric bike individuals', 'private car addicts', and 'public bus enthusiasts' – is identified, each characterized by heterogeneous preferences regarding specific mode attributes and unique socio-demographic profile. The choice model confirms the determinative effects of perceived alternative attributes on commuting mode choice, while the traditionally used objective attributes – travel time and cost – are found to have relatively small influences. The membership model provides solid explanations for these segment-specific preferences. This study provides a better understanding of the nature of mode choice behavior, which can be useful for strategies tailored to a specific segment in order to promote the use of sustainable transport modes.